The dynamics of bond market development, stock market development and economic growth: evidence from the G-20 countries - Pradhan, Rudra P.; Arvin, Mak B.; Norman, Neville R.; Bahmani, Sahar (Universidad ESAN. ESAN Ediciones, 2020)
Purpose: The paper investigates whether Granger causal relationships exist between bond market development, stock market development, economic growth and two other macroeconomic variables, namely, inflation rate and real interest rate. The study aims to expand the domain of economic growth by including a more in-depth analysis of the possible impact that bond market and stock market development has on economic growth than is normally found in the literature. Design/methodology/approach: This paper uses a panel data set of the G-20 countries for the period 1991-2016. It uses a panel vector auto-regression model to reveal the nature of any Granger causality among the five variables. Findings: The paper provides empirical insights that both bond market development and stock market development are cointegrated with economic growth, inflation rate and real interest rate. The most robust result from the panel Granger causality test is that bond market development, stock market development, inflation rate and real interest rate are demonstrable drivers of economic growth in the long run. Research limitations/implications: Because of the chosen research approach, the research results may lack theoretical foundations. Therefore, perhaps the more fully grounded interactive findings of this study can inspire theorists to fill the missing gap. Practical implications – This paper includes lessons for policymakers in the G-20 countries seeking to stimulate economic growth in the long run and how they need to ensure greater stability of the interest rate and inflation rate as well as fully developing their financial markets, as both bond markets and stock markets are obvious drivers of economic growth. Originality/value: This paper fulfills an identified need to study causal relationships between bond market development, stock market development, economic growth and two other macroeconomic variables, i.e. inflation rate and real interest rate.

Objetivo: El documento investiga si existen relaciones causales de Granger entre el desarrollo del mercado de bonos, el desarrollo del mercado de valores, el crecimiento económico y otras dos variables macroeconómicas, a saber, la tasa de inflación y la tasa de interés real. El estudio tiene como objetivo expandir el dominio del crecimiento económico al incluir un análisis más profundo del posible impacto que el mercado de bonos y el desarrollo del mercado de valores tiene sobre el crecimiento económico que el que normalmente se encuentra en la literatura. Diseño / metodología / enfoque: este documento utiliza un conjunto de datos de panel de los países del G-20 para el período 1991-2016. Utiliza un modelo de autorregresión de vector de panel para revelar la naturaleza de cualquier causalidad de Granger entre las cinco variables. Hallazgos: El documento proporciona información empírica de que tanto el desarrollo del mercado de bonos como el desarrollo del mercado de valores están cointegrados con el crecimiento económico, la tasa de inflación y la tasa de interés real. El resultado más sólido de la prueba de causalidad del panel de Granger es que el desarrollo del mercado de bonos, el desarrollo del mercado de valores, la tasa de inflación y la tasa de interés real son impulsores demostrables del crecimiento económico a largo plazo. Limitaciones / implicaciones de la investigación : Debido al enfoque de investigación elegido, los resultados de la investigación pueden carecer de fundamentos teóricos. Por lo tanto, quizás los hallazgos interactivos más plenamente fundamentados de este estudio puedan inspirar a los teóricos a llenar el vacío que falta. Implicaciones prácticas: este documento incluye lecciones para los responsables de la formulación de políticas en los países del G-20 que buscan estimular el crecimiento económico a largo plazo y cómo deben garantizar una mayor estabilidad de la tasa de interés y la tasa de inflación, así como el desarrollo completo de sus mercados financieros, como Los mercados de bonos y los mercados de valores son impulsores obvios del crecimiento económico. Originalidad / valor: Este documento satisface una necesidad identificada de estudiar las relaciones causales entre el desarrollo del mercado de bonos, el desarrollo del mercado de valores, el crecimiento económico y otras dos variables macroeconómicas, es decir, la tasa de inflación y la tasa de interés real.
Keywords: Bond market development; Stock market development; Economic growth; Desarrollo del mercado de bonos; G-20 countries; Desarrollo del mercado de valores; Crecimiento económico; 20 countries; Países del G-20; https://purl.org/pe-repo/ocde/ford#5.02.04